Efficacy and safety of lokivetmab (Cytopoint®) for the control of pruritus and skin lesions in dogs with atopic dermatitis - Pinto,Marta (2022)
ABSTRACT Background and objective: Lokivetmab is the first anti-canine interleukin-31 monoclonal antibody approved in the European Union for Canine Atopic Dermatitis (CAD) management. This study aimed to assess the lokivetmab’s efficacy and safety in treating CAD cases from a university reference service, as well as the dog’s owner’s overall opinion regarding therapy. Methods: Eighteen atopic dogs were enrolled to perform two subcutaneous injections of lokivetmab, according to the protocol. In order to determine the efficacy and safety of the treatment, skin lesions, pruritus score, blood count, liver parameters and adverse side effects were evaluated over 56 days. The overall pet owner’s satisfaction about the therapy was assessed at the end of the study, and the number of animals that maintained the treatment three months after the end of the study was considered. Results: There was a significant reduction in pruritus score over the eight weeks, with 76.5% of the dogs showing a significant clinical improvement. Regarding the lesion score, 77.8% of the dogs achieved significant clinical improvement, with 61.1% reaching it in the first 4 weeks. There were no reported adverse side effects or changes in blood tests. Pet owner’s opinion regarding the improvement of both the dog and its family’s quality of life was very positive, and three months after the end of the study, 77.8% of the dogs continued their therapy with lokivetmab. Conclusion: Lokivetmab proved to be extremely effective and safe, in addition to sparing pet owners from at home drug administrations, which also contributes to their high satisfaction degree. The great specificity of this biological therapy makes it one of the most potente and promising in the CAD field.